GIS-Based Assessment of Soil Erosion Hazard to Support Sustainable Watershed Management in the Mangkang Watershed, Indonesia - Rayza Widyadhana Aprtitaputra; Ussy Andawayanti; Sebrian Mirdeklis Beselly Putra; Aprijanto (Jurnal Penelitian Pendidikan IPA, 2026)
Climate change and land-use change have intensified soil erosion risks in many tropical watersheds, including the Mangkang Watershed in Semarang, Indonesia. This study aims to assess the spatial distribution of soil erosion hazard and identify priority conservation measures using a Geographic Information System (GIS)-based approach integrated with the Universal Soil Loss Equation (USLE). Spatial data on rainfall, soil type, topography, land use, and conservation practices in 2024 were processed in ArcGIS to estimate annual soil loss and classify the Erosion Hazard Index (EHI). The results show that erosion risk varies across the watershed, with high and very high hazard classes mainly concentrated in steep upstream areas, agricultural land, and land-use transition zones with limited vegetation cover. The very high EHI class covered 15.74 km², representing 36.00% of the watershed area. These findings indicate that slope steepness, rainfall erosivity, land-cover conditions, and inadequate conservation practices are the main factors controlling erosion risk. Spatially targeted conservation measures are recommended, including reforestation in degraded upstream areas, terracing and contour farming on steep agricultural slopes, agroforestry development, and riparian buffer restoration along river corridors. This study demonstrates that GIS-based USLE modelling can support sustainable watershed management by identifying erosion-prone areas and guiding site-specific conservation planning.